Molecular characterization and antibacterial activity of a phage-type lysozyme from the Manila clam, Ruditapes philippinarum. Issue 65 (June 2017) - Yang, Dinglong; Wang, Qing; Chen, Lizhu; Liu, Yongliang; Cao, Ruiwen; Wu, Huifeng; Li, Fei; Ji, Chenglong; Cong, Ming; Zhao, Jianmin
Abstract: A phage-type lysozyme, designed as RpPLYZ, was cloned and characterized from the clam Ruditapes philippinarum . The full-length cDNA of RpPLYZ was of 699 bp with an open reading frame (ORF) of 534 bp, encoding a polypeptide of 177-amino acid with a calculated molecular mass of 19.6 kDa and an isoelectric point of 9.05. Multiple alignments and phylogenetic analysis strongly suggested that RpPLYZ was a new member of the phage-type lysozyme family. The mRNA transcript of RpPLYZ was found to be constitutively expressed in a wide range of tissues and mainly in hemocytes and mantle. The relative expression of RpPLYZ mRNA in hemocytes was significantly up-regulated at 6, 24, 48 and 72 h after Vibrio anguillarum challenge. The recombinant RpPLYZ (rRpPLYZ) showed high activity against Entherobacter cloacae and Staphyloccocus aureus, and less effective towards Entherobacter aerogenes and V. anguillarum . Moreover, the optimal pH, temperature and ionic strength for rRpPLYZ activity was determined to be 5.5, 50 °C and 5 mM, respectively. These results suggested that RpPLYZ was a member of the phage-type lysozyme family and perhaps played an important role in the immune responses against bacterial invasion. Highlights: A phage-type lysozyme was identified in the Manila clam, Ruditapes philippinarum. RpPLYZ showed antibacterial activities against both gram-negative and gram-positive bacteria. The optimal pH, temperature and ionic strength for rRpPLYZ was of 5.5, 50 °C and 5 mM, respectively.